The Effect of Firm Size, Leverage, Profitability, Ownership Structure, and Firm Age on Enterprise Risk Management Disclosures - Rujiin, Choiru; Sukirman, Sukirman (Accounting Analysis Journal, 2020)
This study aims to examine the effect of firm size, leverage, profitability, domestic institutional ownership structure, foreign ownership structure, local individual ownership structure, and firm age on enterprise risk management disclosure. The population in this study was a manufacturing firm registered on the IDX in 2013-2017 with a purposive sampling technique and produced 7 samples with 35 units of analysis. The data in this study are secondary data in the form of annual reports with data collection techniques in the form of documentation. This study uses multiple regression data analysis technique. The results showed that firm size and firm age had a significant positive effect on enterprise risk management disclosure, while leverage, profitability, domestic institutional ownership structure, foreign ownership structure, local individual ownership structure had a significant negative effect towards enterprise risk management disclosures. The conclusion of this study is that only firm size and firm age have a significant positive effect on enterprise risk management disclosure, which means that the larger the size of the firm and the longer the firm stands, the higher the disclosure.